Evaluation of Entomopathogenic Fungal Isolate(S) for Management of Melon Fruit Fly (Zeugodacus cucurbitae) (Coquillette) - Onsongo, Susan Kerubo (University of Embu, 2019)
The melon fly, Zeugodacus cucurbitae (Coquillett), is a serious pest of cucurbits, tree fruits and related crops in most continents of the world, including Africa. To manage the pest, most farmers in sub-Saharan Africa rely on synthetic chemicals which have detrimental effects to the environment and the habitat. Excessive use of chemicals may also lead to development of pest resistance and Z. cucurbitae has reportedly shown the most increased resistance to the used insecticides. For sustainable cucurbit production, alternative methods for the management of fruit flies, that are economically sustainable and environmentally friendly, are recommended to reduce overreliance on chemical usage. The objective of this study was to identify and evaluate the best fungal isolate for management of Z. cucurbitae in cucurbits. The virulence of thirteen isolates of Metarhizium anisopliae and two of Beauveria bassiana against Zeugodacus cucurbitae adults was evaluated in the laboratory. Adult fruit ﬂies were exposed to 0.3g of dry conidia, evenly spread on a contamination device and mortality monitored daily. All isolates tested were pathogenic to the adult melon fly and mortality ranged between 20 - 94% at 5 days’ post treatment. The most pathogenic isolates were ICIPE 18, 30 and 69 causing the highest mortality of 87%, 81% and 94% respectively at 5 days’ post treatment. The LT50 values of the most pathogenic isolates ranged between 4–5 days. Two of the most promising isolates were tested on pupa emergence by spraying suspension of different concentration of the selected isolates on soil before introduction of mature (last instar) larvae. The fungi was able to suppress emergence to a range of 3 to 52%. The concentration of 1 x 10 of both ICIPE 18 and 69 isolates was the most effective causing mortality of 53% and 74% respectively. The three selected isolates, were then assessed against Z. cucurbitae adults at temperature regimes of 15, 20, 25 and 30°C. The optimum temperature for all isolates was found to be 25 and 30°C. Mortality from the three isolates ranged between 28.8% and 90% across the different temperatures. The isolates ICIPE 69 and ICIPE 18 recorded the highest mortality of 82% and 90% and the shortest LT50 values of 2.61 and 2.63 days, respectively, at 30°C. However, ICIPE 69 had the highest conidia production of 90.5 x 10 8 7 ml/10 at 30°C and was therefore selected for global mapping to predict its efficacy against Z. cucurbitae using the geospatial temperature data layer and the best fitted quadratic model. The map showed that the isolate would be highly effective in the tropics than in temperate climates. Laboratory tests confirmed compatibility of the selected ICIPE 69 isolate with 7 Cue-lure, a commercially available attractant on adult melon fly. In addition, laboratory bioassay to test the potential for horizontal transmission showed that males and females exposed to M. anisopliae conidia (donors) became infected and exhibited 100% mortality. The recipients resulted to male and female mortality of 97% and 86% respectively, after 10 days of exposure, thus confirming the ability of fruit flies to transmit inoculum to other flies. It was also shown that the fungus affects the number of eggs oviposited, although the hatchability is not affected. This therefore identifies ICIPE 69 as a potential isolate for the management of melon fly with effective results at optimum temperatures and can be used together with the Cue-lure in the field set up.
A Thesis Submitted in Partial Fulfillment of the Requirements for the Award of The Degree of Master of Science on Horticulture of The University of Embu
Keywords: Fungal Isolates; melon fruit